(untitled) (Jurnal Proaksi, 2022)
There has been an ethical violation committed by a tax consultant, there by reducing the integrity and professionalism which is the code of ethics in carrying out his profession. Ethical violations here involve ethical decision making, even the decisions taken are contrary to the applicable tax laws. The purpose of this study was to determine the factors that influence the ethical decision making of tax consultants. This type of research is explanatory with the data collection method using a questionnaire. The population in this study were all registered tax consultants at the Surabaya branch of IKPI, while the sample was 84 respondents. The sample in this study was determined by probability sampling type, the sample was taken using a simple random sampling technique. The data analysis used partial least square. The results of this study indicate that love of money and self-efficacy have a positive effect on ethical decisions, while locus of control and gender do not effect on ethical decisions of tax consultants. Keywords: Self Efficacy, gender, Ethical Decisions